Re-Design Manajemen Pendidikan Anak Usia Dini Berbasis Emotional Quotient - Mohammad Thoha; Hilmi Qosim Mubah (Institut Agama Islam Negeri Madura, 2023)
The world of education in this era is trapped in a pragmatic mindset in almost all sectors. Educators and education staff, students, financing, learning processes, fulfillment of infrastructure, assessment, and management services seem to work following a mechanical pattern and deny humanistic elements of humans which are full of politeness, patience, cooperation, mutual understanding, and so on. This research uses the Systematic Literature Review (SLR) method with a choice of Preferred Reporting Items for Systematic Reviews and Meta-analyses or PRISMA. The results of this study show that emotional intelligence as a basis for implementing early childhood education management can positively affect educators and education staff. The values of emotional intelligence which include the ability to motivate oneself, resistance to frustration, self-control, and the ability to balance emotions and ratios will lead the entire educational community to enjoy a harmonious, humane, and warm educational process.